EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK TEKNIK DECISION MAKING MODEL DALAM KEMATANGAN KARIR SISWA DI SMA NEGERI 1 KECAMATAN PAYAKUMBUH - Ririanti, Yulisa; Masril; Irman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Career maturity helps students make good career choices by considering their interests, skills, and what jobs might be available in the future. Many senior high school students still have trouble figuring out how to plan and choose their future careers. This study tried to see how well group guidance using the Decision Making Model technique helps students develop their career maturity. The study used a pre-experimental approach where only one group was tested before and after the intervention. The group included ten high school seniors from SMA Negeri 1 Kecamatan Payakumbuh, who were chosen using a random selection method. Data was gathered through a career maturity scale and then looked at using a paired samples t-test and N-Gain analysis. The results showed that the average score before the test was 104.9, which is in the moderate range, and it went up to 139.1, which is in the high range, after the test. The t-test comparing the scores before and after the intervention showed a significant improvement (t = 4.746; p < 0.05), meaning the intervention had a clear positive effect on students' career maturity. The N-Gain score of 0.52 showed a moderate amount of improvement. These results show that using group guidance with the Decision Making Model helps students develop their career maturity, especially in areas like planning their careers, exploring different career options, making decisions, learning about jobs, and understanding different types of work.